Cdc42 and RhoA reveal different spatio-temporal dynamics upon local stimulation with Semaphorin-3A - Iseppon, Federico; Napolitano, Luisa M.; Torre, Vincent; Cojoc, Dan (Frontiers in Cellular Neuroscience, 2015)
Small RhoGTPases, such as Cdc42 and RhoA, are key players in integrating external cues and intracellular signaling pathways that regulate growth cone (GC) motility. Indeed, Cdc42 is involved in actin polymerization and filopodia formation, whereas RhoA induces GC collapse and neurite retraction through actomyosin contraction. In this study we employed Förster Resonance Energy Transfer (FRET) microscopy to study the spatio-temporal dynamics of Cdc42 and RhoA in GCs in response to local Semaphorin-3A stimulation obtained with lipid vesicles filled with Semaphorin-3A and positioned near the selected GC using optical tweezers. We found that Cdc42 and RhoA were activated at the leading edge of NG108-15 neuroblastoma cells during spontaneous cycles of protrusion and retraction, respectively. The release of Semaphorin-3A brought to a progressive activation of RhoA within 30 seconds from the stimulus in the central region of the GC that collapsed and retracted. In contrast, the same stimulation evoked waves of Cdc42 activation propagating away from the stimulated region. A more localized stimulation obtained with Sema3A coated beads placed on the GC, led to Cdc42 active waves that propagated in a retrograde manner with a mean period of 70 seconds, and followed by GC retraction. Therefore, Semaphorin-3A activates both Cdc42 and RhoA with a complex and different spatial-temporal dynamics.